The Relationship Between Communication Patterns In The Family To The Expressive Language Ability Of Children At The Age Of 5-6 Years - Ade Nurlita Ahmad; Halida, Halida; Lukmanulhakim (Jurnal Pendidikan Anak, 2024)
The role of the family in the development of children's language is also very influential, because the family is the first and main environment for children to learn, especially fathers and mothers. Parents have a role to help children complete their developmental tasks including developing language skills. Every parent's actions in the family and social environment will have an influence on the development of children's language. Parents are the first people to engage and interact with children so parents are considered the first teachers for children. Positive communication between parents and children can shape a child's language development. The purpose of this study is to analyze the relationship between communication patterns in the family and expressive language skills in children aged 5-6 years at TKIT Al-Mumtaz. Using the correlational research method, the use of the correlational method in this study is because it examines the relationship or correlation between two variables.